Cardiovascular disease risk assessment, exercise training, and management of complications in patients with chronic kidney disease - Francesco Perone; Marco Bernardi; Monica Loguercio; Francesca Jacoangeli; Silvia Velardi; Theodora Metsovitis; Federica Ramondino; Matteo Ruzzolini; Marco Ambrosetti (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Patients with chronic kidney disease are at high and very high risk of cardiovascular disease. As estimated glomerular filtration rate declines, the incidence and severity of risk factors, complications, and atherosclerotic cardiovascular events increase. In this scenario, tailored assessment is the key to evaluate the severity of chronic kidney disease and estimate cardiovascular disease risk. Personalized stratification differentiates patients with chronic kidney disease without diabetes mellitus or established atherosclerotic cardiovascular disease in their management and beneficial treatment. Exercise intensity assessment and prescription is suggested to propose specific and safe recommendations for physical activity, training, and cardiac rehabilitation. Programs are based on a combination of endurance and resistance exercise and should be adapted to very high risk chronic kidney disease and haemodialysis patients and after kidney transplantation. Appropriate management of cardiovascular complications in these patients, such as risk factors, heart failure, arrhythmias, and coronary artery disease, is essential to ensure the best treatment and improve the prognosis. Therefore, we propose a critical and comprehensive review to suggest how to manage patients with chronic kidney disease in clinical practice and, specifically, with regard to cardiovascular risk assessment, exercise training prescription, and management of complications.